2017
DOI: 10.18632/oncotarget.14999
|View full text |Cite
|
Sign up to set email alerts
|

Stromal fibroblasts present in breast carcinomas promote tumor growth and angiogenesis through adrenomedullin secretion

Abstract: Tumor- or cancer-associated fibroblasts (TAFs or CAFs) are active players in tumorigenesis and exhibit distinct angiogenic and tumorigenic properties. Adrenomedullin (AM), a multifunctional peptide plays an important role in angiogenesis and tumor growth through its receptors calcitonin receptor-like receptor/receptor activity modifying protein-2 and -3 (CLR/RAMP2 and CLR/RAMP3). We show that AM and AM receptors mRNAs are highly expressed in CAFs prepared from invasive breast carcinoma when compared to normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 60 publications
0
43
0
Order By: Relevance
“…In order to positively participate in neo-angiogenesis, human breast CAFs deposit and secrete more adrenomedullin (AM) compared with normal fibroblasts. AM blockade is able to impair tumor vascular formation and induce apoptosis (115). Notch signaling is an evolutionarily conserved pathway that regulates cell biological characteristics, whose accommodative dysfunction has been implicated in various tumors.…”
Section: Molecular Signaling Pathways By Which Cafs Promote Tumor Neomentioning
confidence: 99%
“…In order to positively participate in neo-angiogenesis, human breast CAFs deposit and secrete more adrenomedullin (AM) compared with normal fibroblasts. AM blockade is able to impair tumor vascular formation and induce apoptosis (115). Notch signaling is an evolutionarily conserved pathway that regulates cell biological characteristics, whose accommodative dysfunction has been implicated in various tumors.…”
Section: Molecular Signaling Pathways By Which Cafs Promote Tumor Neomentioning
confidence: 99%
“…Accumulating evidence suggests that both stromal fibroblasts and CSCs mediate tumor growth and metastasis (Benyahia et al, 2017; Elkabets et al, 2011; Ghesquiere et al, 2014; Mao et al, 2013; Tripathi et al, 2012). Since these components have a direct influence in the TME of these reproductive cancers, they represent attractive targets for therapeutic development.…”
Section: Tumor Cell Interactions With the Mesenchymementioning
confidence: 99%
“…Although the differences were not signi cant, we did nd a stronger in ammatory response in the DM than in the non-DM group, suggesting that AM expression in response to in ammation may be more closely related to the development of diabetes in PC patients, as reported previously 6 7 17 . Regarding broblasts, Bhowmick et al 18 showed that stromal broblasts in tumors are biologically distinct from normal broblasts, and Benyahia et al 19 reported that stromal broblasts in breast cancer promote tumor growth and angiogenesis through AM secretion. We expect that the AM expression of stromal broblasts in PC will be found to have multiple functions and to be associated with the onset of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In the DM and non-DM groups, respectively, median serum CA19-9 was 724 and 1,144 U/ml, median amylase was 58 and 72 IU/l, and median CRP levels were 0.14 and 0.12 mg/dl. The number of signi cant dilatations ≥ 5 mm in diameter of the main pancreatic duct was 11 52 and 9 33 in the DM and non-DM groups, respectively, whereas the number of patients in the DM and non-DM groups with invasion to the portal vein was 4 19 and 9 33 , respectively, and 5 24 and 15 56 patients, respectively, had liver metastases. The number of clinical Stage cases in the DM and non-DM groups was 14 67…”
Section: Clinicopathological Comparisons Between the Dm And Non-dm Grmentioning
confidence: 96%